Between Past and Future - 2/7
Continuation of the third panel “Winners and Losers in the Great Transformations Since 1989” from the "Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference organized by CEU and the University of Maryland, held at CEU between 26th and 28th of March, 1999. Chairman of the panel is Academic Pro-Rector and CEU Professor Sorin Antohi. Speakers of the panel are Adam Michnik (Editor, Gazeta Wyborcza, Poland), Martin Palous (Deputy Foreign Minister of the Czech Republic), Valerie Bunce (Professor at Cornell University), János Kis (Professor at CEU), Jeffrey Isaac (Professor at Indiana University) and Vladimir Tismăneanu (Professor at Maryland University). The tape contains excerpts from Martin Palous', Valerie Bunce's, János Kis', Jeffrey Isaac's and Vladimir Tismăneanu's presentations. It also contains fragments from the Q&A session that followed the presentations.